2019
DOI: 10.1186/s12864-019-5938-0
|View full text |Cite
|
Sign up to set email alerts
|

The haustorial transcriptome of the cucurbit pathogen Podosphaera xanthii reveals new insights into the biotrophy and pathogenesis of powdery mildew fungi

Abstract: Background Podosphaera xanthii is the main causal agent of powdery mildew disease in cucurbits and is responsible for important yield losses in these crops worldwide. Powdery mildew fungi are obligate biotrophs. In these parasites, biotrophy is determined by the presence of haustoria, which are specialized structures of parasitism developed by these fungi for the acquisition of nutrients and the delivery of effectors. Detailed molecular studies of powdery mildew haustoria are scarce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 77 publications
(104 reference statements)
0
26
0
1
Order By: Relevance
“…The high expression of PxLPMO1 , which was the 13th most highly expressed gene in the haustorium and the most highly expressed gene among the genes encoding haustorium‐specific secreted proteins (Polonio, Seoane, et al., 2019), suggested that it plays an important role in P. xanthii biology. To validate the role of PxLPMO1 , the Agrobacterium tumefaciens ‐mediated host‐induced gene silencing (ATM‐HIGS) assay was used.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The high expression of PxLPMO1 , which was the 13th most highly expressed gene in the haustorium and the most highly expressed gene among the genes encoding haustorium‐specific secreted proteins (Polonio, Seoane, et al., 2019), suggested that it plays an important role in P. xanthii biology. To validate the role of PxLPMO1 , the Agrobacterium tumefaciens ‐mediated host‐induced gene silencing (ATM‐HIGS) assay was used.…”
Section: Resultsmentioning
confidence: 99%
“…xanthii (Polonio, Seoane, et al, 2019) allowed us to identify an effector candidate, PHEC27213, that had typical effector features, such as no annotated function, a small size, and a wave-like expression pattern (Hacquard, 2014;Pedersen et al, 2012). Furthermore, PHEC27213 was the most highly expressed, haustorium-specific, putative secreted protein (Polonio, Seoane, et al, 2019), pointing to its key role in haustorial physiology. In this work, we performed a molecular characterization of PHEC27213 to elucidate its putative function as a chitin manipulation-related protein.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations